Thermoplastic multifunctional polysiloxane-based materials from broad gradient-transition multiphase separation. Issue 32 (29th July 2020) - Fan, Jianfeng; Huang, Jiarong; Yan, Mengwen; Gong, Zhou; Cao, Liming; Chen, Yukun
Abstract : The current work demonstrates broad gradient-transition multiphase separation for thermoplastic polysiloxane-based polymers, featuring mechanical robustness, shape memory property and healing-ability. Abstract : The current work demonstrates broad gradient-transition multiphase separation for thermoplastic polysiloxane-based polymers, featuring mechanical robustness, shape memory property and healing-ability. Conventional thermoplastic elastomers are generally fabricated by embedding hard nanodomains as physical crosslinks into a soft matrix. However, it is difficult to achieve shape-memory capability in polysiloxane-based polymers with this structure because polysiloxane chains have low glass transition temperature ( T g ) and are non-crystalline with little capacity to store the entropy energy after deformation. Herein, by taking advantage of the thermodynamic incompatibility between polysiloxane and polyimide, as well as the chain rigidity and linearity of polyimide, a novel poly(imide siloxane) polymer is developed, in which the flexible polysiloxane segments curled into soft nanodomains on low T g, with increasing T g towards the glassy polyimide matrix. The formed gradient-transition layers served as switch segments to trigger shape recovery, maintain a temporary shape and the innermost hard segments were assembled into netpoints with the assistance of gradient layers to prevent chain slippage. The disassociation of the inferior intermolecular interactions within the gradient-transition layers and the quasi-permanent crosslinking of the innermost nanodomains with the highest T g synergistically endowed polymers with heat-assisted self-healing ability. Moreover, the hard matrix provided a protective barrier against external forces, leading to high mechanical robustness. Based on these features, we believe that these polymers are advantageous for various applications, such as implants, vascular stents and other medical devices.